Nanotechnology for Hepatocellular Carcinoma: From Surveillance, Diagnosis to Management - Wu, Han; Wang, Ming‐Da; Liang, Lei; Xing, Hao; Zhang, Cheng‐Wu; Shen, Feng; Huang, Dong‐Sheng; Yang, Tian (Small (Weinheim an der Bergstrasse, Germany), 2021)
Hepatocellular carcinoma (HCC) remains the fourth leading cause of cancer‐related death worldwide. However, the clinical diagnosis and treatment modalities are still relatively limited, which urgently require the development of new effective technologies. Recently, nanotechnology has gained extensive attention in HCC surveillance, imaging and pathological diagnosis, and therapeutic strategies. Typically, nanomedicines have been focused on early HCC diagnosis and precise treatment of advanced HCC, which has developed and improved a variety of new technologies and agents for future clinical practice. Furthermore, strategies of facilitating drug release and delivery in current treatment processes such as ablation, systematic therapy, transcatheter arterial chemoembolization, molecular targeted therapy, and immune‐modulating therapy have also been studied widely. This review summarizes the recent advances in this area according to current clinical HCC guidelines: 1) Nanoparticle‑based HCC surveillance; 2) Nanotechnology for HCC diagnosis; 3) Therapeutic advances for HCC Management; 4) Limitations of applications in nanotechnology for HCC; 5) Conclusions and perspectives. Although there are still many limitations and difficulties to overcome, the investigations of nanomedicines are believed to show potential applications in clinical practice. Schematic illustration of nanotechnology development for hepatocellular carcinoma (HCC). The advancement of nanotechnology actually runs through the whole process of HCC surveillance, diagnosis, and clinical management. In addition to monitoring tumor markers such as α‐fetoprotein detection, assisting imaging diagnosis and traditional treatment, many promising new nano‐strategies like immune regulator are emerging.